Analisis kondisi likuidistas perusahaan FMCG (Studi kasus PT Mayora) - Budi Dharma; Andriani Sahputri; Nadya Maulidya M (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The intent or purpose of conducting this research is to analyze or also find out the results of predicting the situation in a company from the analysis of the financial statements that they have, and the company that the author uses for the case study is PT. Mayora uses the research method using the method of analysis, namely quantitative descriptive analysis, using the use of a system to collect data or information, namely such as a library data collection system which is a component of literature study, therefore the type and journal data come from data that has been get is secondary data. And the research results from this journal result that starting from 2019-2021 the value of the current ratio of PT. Mayora shows that the position of the company's financial performance is in a liquid position. Where it can be seen that the intention of the liquid position is the position of assets that have sufficient cash or assets that are very sufficient to be liquidated into cash to meet needs.